Comparison of the scleral tunnel constructed with crescent versus razor blade using the anterior segment optical coherence tomography - Sowmya Raveendra Murthy; Priyanka Sudhakar (Kerala Journal of Ophthalmology, 2020)
Aim: The aim of this study is to compare and contrast the efficacy of a razor blade against crescent, in constructing a scleral tunnel in temporal small-incision cataract surgery (SICS) in a community setup. The following parameters were considered for the comparative analysis: a) Structural anatomical dimensions using the anterior segment optical coherence tomography (ASOCT), b)Tunnel integrity based on the need for suturing or subsequent resuturing and c) Section outcome in terms of any associated tunnel complications. Methods: A prospective, comparative study of 100 consecutive cases of temporal SICS was done. The cases were randomly divided to undergo the surgery with tunnel construction either with a crescent knife or a razor blade (50 eyes each), by a singleoperating surgeon (Dr SR). The structural dimensions and integrity of the tunnel were noted using an AS-OCT on the 1st postoperative day. Tunnel-related complications were noted both intra and postoperatively. Results: Of the 100 eyes operated, the mean average depth at section, with crescent was found to be 526 μ, while that with blade was 598 μ. The mean average depth at internal entry was found to be 607 μ with crescent and that with blade was 670 μ. Self-sealing wound was achieved in 49 of the 50 cases with crescent as well as with blade, with only 1 tunnel requiring 1 suture for anterior chamber (AC) formation in case of both crescent and blade. Tunnel complications included Descemet's membrane detachment in 1 eye and premature entry in 1 eye, in razor blade constructed tunnel. The time taken with crescent was on a mean average 32.9 s, while that with blade was 27.3 s. Conclusion: Razor blade constructed scleral tunnels are slightly deeper compared to crescent as noted on AS-OCT. Integrity and complication rates being comparable between the two. The razor blade could be considered as a safe, equally efficacious, if not better, and an economical alternate to crescent knife in a high-volume community setup.